The Influence Of The Islamic Capital Market On Indonesia's Economic Growth: Correlation Quantitative Analysis And Fiqh Wahbah Zuhaili Perspective - Danial Muhammad Wirdyansyah; Vaira Nur Zahra; Obin; Putri Tasela Ayu (ISTIKHLAF: Jurnal Ekonomi, Perbankan dan Manajemen Syariah, 2025)
As a country with a generally Muslim population, Indonesia isn't vulnerable to the challenges posed by global query, and the Islamic capital request is one of the most effective indispensable instruments for developing public profitable growth. This study was conducted to ascertain the effectiveness of the Islamic capital request in adding profitable growth, and the exploration gap linked was the inconsistency of exploration results and the limited data sample, which only extends up to 2023. To address this exploration gap, this study utilized Islamic capital request data from 2015 to 2024 on a yearly basis, employing multiple direct retrogression analysis to minimize the eventuality for crimes that may have been overlooked by former researchers. The findings indicate that all independent variables ply a partial and contemporaneous influence on the dependent variable. This conclusion is farther substantiated by an analysis of fiqh literature, particularly from the perspective of Wabah Zuhaili, which demonstrates that the Islamic capital request is an effective instrument for enhancing public profitable growth.